THE CURRENT CHRONIC OBSTRUCTIVE PULMONARY DISEASE SITUATION IN THE REPUBLIC OF SAKHA (YAKUTIA) - A. I. Sivtseva; A. V. Strutynsky; F. A. Platonov; T. S. Neustroeva; M. A. Ivanova (Туберкулез и болезни лёгких)
The prevalence of respiratory diseases was analyzed in the Republic of Sakha (Yakutia). A cross-sectional clinical and instrumental study of 2856 dwellers from the town of Yakutsk and the village of Churapcha showed that the proportion of chronic obstructive pulmonary diseases (COPD) was 14.1 and 20.5% in the town and in the village, respectively. One of its chief causes is a considerable spread of tobacco smoking among the urban and rural dwellers of Yakutia. The incidence of COPD among the males aged over 60 years was higher than that in the women; that was almost 2-fold in the rural area; and the male-to-female ratio was nearly equal in the urban area. According to our data, the urban and rural rates of catarrhal diseases were 54.5 and 43.9%, respectively; which was also due to severe climatic conditions and one of the risk factors for COPD.